The millennial hospitality graduates commitment toward hotel industry career: diagnosing causes of the causations / Feri Ferdian - Ferdian, Feri (2021)
It is without doubt that the future success of the hotel industry is still well depends on the youth, hospitality program and the industrial training. An enthusiastic, committed workers and employees are seen as vital attributes of a successful business in any industry including hotel and employee’s commitment will be determined not only by their intention to work but to stay longer in the industry. Education, training, skills and motivation of the graduates play a key role in attaining their commitment to work in the industry. Scholar argued that curriculum design, hallmark of the industry, modelling by others and social persuasion not only act as career influencers for students in enrolling into a specific career program but could also determine graduate’s commitment toward long term career. However, the existing literature has neglected the experiences of the millennial hospitality graduates’ commitment toward long career hotel industry and the factors that causes the causations. Thus, in understanding and filling the gap, this study examines the influence of hospitality career influencers attributes on the millennial hospitality program graduate’s commitment toward career in the hotel industry. This study is structured through a self-administered and online questionnaire survey with the individual’s hospitality graduates who are currently working in the 3 to 5-star hotels in the 14 selected tourism development provinces in Indonesia. The graduates experienced was tapped using a quantitative approach. A total 880 usable questionnaires were successfully collected. With the various statistical analyses ranging from frequency, descriptive, inferential and the Multivariate Structural Equation Modeling (SEM) via Partial Least Square (PLS- SEM) used to answer the objectives, research questions and hypotheses, some useful insights pertaining to the issues investigated was significantly obtained. It is evident that curriculum design, hallmarks of the hotel industry, social persuasion and modelling by others as part of hospitality career influences do clearly show the causation of how the millennials hospitality graduates report their view about commitment toward career in the hotel industry. In fact, the millennials hospitality graduates’ commitment toward career in the hotel industry is apparently directly related to these independent variables except the social persuasion. In addition, the millennials hospitality graduates perceived that the curriculum design, hallmarks of the hotel industry and modelling by others significantly giving benefits towards their career and most importantly the millennial culture has given a negative indicator on the millennial hospitality graduate’s commitment toward career in the hotel industry. These findings clearly provide significant insights and lead to varying consequences for the hospitality graduates, hospitality institutions, industry and the government as a whole.